Preface: Education and Society - Nurmila, Nina (Muslim Education Review, 2022)
Publishing articles in scholarly journals is an unavoidable activity for academics. Some courses require postgraduate students to publish in a journal in order to pass their classes. Some Indonesian institutions require students to publish articles in a journal before graduation and journal publication has become one of the requirements for lecturers to be promoted into a higher-ranked job. Out of these obligations, there are many benefits of publishing articles in a journal. One of these is that our thoughts and expertise will be conveyed to the public. This will attract further benefits such as being invited to be the speaker on the topic about which we have written or being invited to collaborate on further research and publications.